Factors influencing the perception of youth agro-based entrepreneurs towards the role of ICT in increasing agro-business productivity - Hassan, Md. Salleh; Mohamed Shaffril, Hayrol Azril; Abu Samah, Bahaman (Directorate of Agricultural Information Punjab, 2012)
Information and Communication Technology (ICT) usage has become more common in this modern age and agriculture is one of the sectors that benefited from it. Based on this, a study was conducted at Institute of Social Sciences, University Putra Malaysia, Serdang, Selangor Darul Ehsan, Malaysia during the year 2007-08 to know the perception of Malaysian youth agro-based entrepreneurs towards the ICT contribution to their agro-business productivity. Moreover, this study tried to discover the factors that affected this perception. The study covered all states in Peninsular Malaysia. Simple random sampling was used for sampling while face-to-face interviews using trained enumerators were conducted to collect required data. For analysis, SPSS software was used with application such as frequency, mean, percentage, standard deviation, independent t-test, ANOVA, Pearson correlation and multiple linear regression. In all 134 youth agro-based entrepreneurs were interviewed. Majority of respondents perceived a high contribution of ICT towards their agro-business productivity. The result revealed no significant difference in perception on ICT contribution between zones, gender and level of education. Three factors viz. age, electronic media usage and ICT usage were found to have significant relationship with perception towards ICT usage while age was found to be the highest contributor in perception towards ICT contribution.